2014
DOI: 10.1038/srep05340
|View full text |Cite
|
Sign up to set email alerts
|

Novel common variants and susceptible haplotype for exfoliation glaucoma specific to Asian population

Abstract: The common variants in lysyl oxidase-like 1 gene (LOXL1) are associated with exfoliation glaucoma (XFG) patients developed through exfoliation syndrome (XFS). However, the risk allele of a variant in LOXL1 has been found to be inverted between Asian and Caucasian populations. Therefore, we newly performed a genome-wide association study using 201 XFS/XFG and 697 controls in Japanese, and identified 34 genome-wide significant single-nucleotide polymorphisms (SNPs) distributing in not only LOXL1 but also TBC1D21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 24 publications
0
28
0
7
Order By: Relevance
“…Research on the genetic risk factors for XFS is an area of intense research, and other susceptibility loci and SNPs have been identified in association with this syndrome in certain populations (Krumbiegel et al 2011;Wiggs et al 2012;Nakano et al 2014;Zagajewska et al 2018;Ma et al 2019). Genomewide association study (GWASs) and next-generation sequencing technologies have been used to elucidate potential genetic causal variants underlying XFS, which could help better understanding the disease mechanism and provide specific treatment approaches (Schl€ otzer-Schrehardt 2018).…”
Section: Genetic Factors: Clumentioning
confidence: 99%
“…Research on the genetic risk factors for XFS is an area of intense research, and other susceptibility loci and SNPs have been identified in association with this syndrome in certain populations (Krumbiegel et al 2011;Wiggs et al 2012;Nakano et al 2014;Zagajewska et al 2018;Ma et al 2019). Genomewide association study (GWASs) and next-generation sequencing technologies have been used to elucidate potential genetic causal variants underlying XFS, which could help better understanding the disease mechanism and provide specific treatment approaches (Schl€ otzer-Schrehardt 2018).…”
Section: Genetic Factors: Clumentioning
confidence: 99%
“…Realizing that large and inclusive international collaborative efforts are essential in providing new biological leads in complex disease pathogenesis [15][16][17][18][19][20] , we report here a world-wide collaborative XFS study aimed at further understanding the genetic basis of the disorder. Firstly, due to the allele reversals seen at LOXL1 common polymorphisms led by rs3825942 G>A (p.153Gly>Asp) and to a lesser extent, rs1048661 T>G (p.141Leu>Arg) 12,[21][22][23][24][25][26][27][28] (Supplementary Figure 1), we aimed to refine the LOXL1 genetic landscape by performing deep sequencing of the entire gene in 5,570 XFS and XFG cases and 6,279 controls from 9 countries (Supplementary Table 1). The previously reported CACNA1A locus was also sequenced to assess if rare non-synonymous amino acid substitutions within the gene could provide further insights [29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…LOXL1 codes for an enzyme that is essential for the formation, maintenance, and remodeling of elastic fibers and prevents age-related loss of tissue elasticity. The association of LOXL1 with XFS has been confirmed in populations from throughout the world including Asian populations of Chinese, Indian, and Japanese [186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205]. The association of LOXL1 with XFS has been confirmed in populations from throughout the world including Asian populations of Chinese, Indian, and Japanese [186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205].…”
Section: Exfoliation Syndrome Glaucomamentioning
confidence: 99%